Glyptosceloides dentatus, a genus and species of eumolpinae new to Chile (Coleoptera: Chrysomelidae) - Askevold, I.S.=700 1 Wills Flowers, R.
(Es, En)
Ilus., 8 ref.
Keywords: COLEOPTERA; CHRYSOMELIDAE; ESPECIES NUEVAS; IDENTIFICACION; CHILE; GLYPTOSCELOIDES DENTATUS; REVISTA CHILENA DE ENTOMOLOGIA